Pengaruh Proses Penilaian Kinerja Pengembangan Karir dan Spesifikasi Kerja Terhadap Motivasi Pegawai di Kantor Pelayanan Pajak Pratama - Dora Mauren Asianita; Hensty Simorangkir; Budiman Arif; Ananda Satria Merqurius Bessie; Riska Yanti; Nur. M. Ridha Tarigan; Nilawati Nasti; Sri Gustina Pane (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the effect of performance appraisal process, career development and work specifications partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama. The study was conducted at the Kantor Pelayanan Pajak Pratama, with a population of 103 people, and a study sample. of 50 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained performance appraisal process have a positive and significant effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama, this is supported by the results of t count analysis > t-table (2,095 > 2,014) at n = 50 at 95% significance level. Career development has a not effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama, this is supported by an analysis of t count > t-table (2,457 > 2,014) at n = 50 at 95% significance level. Work specifications has a not effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama, this is supported by an analysis of t count < -table (1,430 < 2,014) at n = 50 with a significant level of 95%. Value of F-count> F table (24,325 > 2,81) This states that together (multiple) there are positive and significant effects of performance appraisal process, career development and work specifications on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama. Thus the hypothesis proposed is accepted by the truth